2016
DOI: 10.5812/jjm.41030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Candida species with Emphasis on Predisposing Factors in Cutaneous Candidiasis Patients

Abstract: Background: Candida species are known as the most common fungal pathogens isolated from clinical specimens that can develop complications ranging from cutaneous to systemic diseases. Objectives: The present study was conducted to evaluate the diversity and distribution of Candida species in various kinds of cutaneous candidiasis in Tehran, Iran. In addition, the critical effects of several predisposing factors on the induction and progression of the disease were considered. Methods: A total of 3000 samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
4
3
0
Order By: Relevance
“…Considering further chance for hands in contact with pollution sources and the effect of some epidemiological elements such as occupational factors, the increased chance of yeasts isolation from this anatomical site is explainable. Isolation of C. parapsilosis as the commonest species (35%) in all sites of the skin in our study was noteworthy which was consist with other studys about candida colonization [13,14]. As other surveys that determined C. albicans seldom lives saprophitically on the skin [7] we found that C. albicans is one of the least inhabitants of the skin, whereas new studied showed among Candida species, C. albicans is still the most common infectious agent isolated from clinical samples in Iran and the word [13,15].…”
Section: Discussionsupporting
confidence: 91%
“…Considering further chance for hands in contact with pollution sources and the effect of some epidemiological elements such as occupational factors, the increased chance of yeasts isolation from this anatomical site is explainable. Isolation of C. parapsilosis as the commonest species (35%) in all sites of the skin in our study was noteworthy which was consist with other studys about candida colonization [13,14]. As other surveys that determined C. albicans seldom lives saprophitically on the skin [7] we found that C. albicans is one of the least inhabitants of the skin, whereas new studied showed among Candida species, C. albicans is still the most common infectious agent isolated from clinical samples in Iran and the word [13,15].…”
Section: Discussionsupporting
confidence: 91%
“…Candida albicans was reported as the most isolated species from infected patients in this study and other studies in Asian, European, and American countries (3,5,(11)(12)(13)(14). A global increase was seen in the number of infections caused by species other than C. albicans, including C. tropicalis, C. parapsilosis, C. glabrata, and C. krusei (8,15).…”
Section: Discussionsupporting
confidence: 61%
“…In epidemiological studies, most of the yeast isolates belong to Candida species, especially C. albicans (1,4,5,17,18). Previous studies in different regions of Iran show that Candida species were isolated from various clinical samples rather than other yeasts (2,5,(18)(19)(20)(21)(22)(23). As already mentioned in most studies, among Candida species, C. albicans, C. parapsilosis, C. tropicalis, C. glabrata, and C. krusei were the most common causes of candidiasis in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of fungal infections caused by yeasts and yeast-like species, particularly the genus of Candida, significantly increased due to extensive application of immunosuppressive drugs, predisposing factors, and particular conditions. Some rare and uncommon yeast species emerged as a cause of outbreak with high mortality or mixed infections non-responsive to routine antifungals (1,2). Clinical manifestations of yeasts and yeast-like infections ranging from mild superficial to systemic infections are frequently and usually benign in immunocompetent individuals (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation